Diseno estructural - Riddell, Rafael (Ediciones UC, 1997)
The purpose of this book is to provide an overview of the problem of structural design. For this, a wide set of design cases is presented, considering different types of internal forces or stability conditions, different structural materials, including both their elastic and inelastic behavior ranges, and the two basic design models: the admissible stress method. and design for resistance.